2017
DOI: 10.1021/acs.langmuir.7b01759
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fast Synthesis of Nanoparticles for MRI: Coating Chemistry as the Key Variable Determining Positive or Negative Contrast

Abstract: Iron oxide nanomaterial is a typical example of a magnetic resonance imaging probe for negative contrast. It has also been shown how this nanomaterial can be synthesized for positive contrast by modification of the composition and size of the core. However, the role of the organic coating in the relaxometric properties is largely unexplored. Here, maghemite nanoparticles with either excellent positive or very good negative contrast performance are obtained by modifying coating thickness while the core is kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(91 citation statements)
references
References 53 publications
9
82
0
Order By: Relevance
“…After these first approaches, better longitudinal relaxivities were observed using sodium citrate as surfactant. In this case, an increase in the temperature of the reaction turns over the contrast capabilities from T 2 to T 1 with an r 1 = 11.9 mM −1 s −1 at 1.5 T when the reaction is performed at 120 • C [81]. Very recently, Fernandez-Barahona et al increased this value up to 15.7 mM −1 s −1 , doping the iron oxide core with 4% mol of Cu [99].…”
Section: Microwave Assisted Synthesismentioning
confidence: 97%
See 1 more Smart Citation
“…After these first approaches, better longitudinal relaxivities were observed using sodium citrate as surfactant. In this case, an increase in the temperature of the reaction turns over the contrast capabilities from T 2 to T 1 with an r 1 = 11.9 mM −1 s −1 at 1.5 T when the reaction is performed at 120 • C [81]. Very recently, Fernandez-Barahona et al increased this value up to 15.7 mM −1 s −1 , doping the iron oxide core with 4% mol of Cu [99].…”
Section: Microwave Assisted Synthesismentioning
confidence: 97%
“…In this regard, different coatings such as small molecules, macromolecules or proteins have served as stabilisers [77][78][79][80]. In addition, the size of the coating has been demonstrated to be a key factor in the T 1 effect [81]. Large size coatings (i.e., large hydrodynamic size, >30-40 nm) restrict water access to the nanoparticle core increasing the outer-sphere contribution to the relaxation mechanism.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…This drawback has focused research on finding methods for developing IONPs that serve as positive contrast agents for T1-weighted MRI. Studies have demonstrated that the downsizing of IONP core or coating thickness causes a shift on the NP magnetic behavior from superparamagnetic towards paramagnetic, thus creating T1-weighted MRI contrast agents [72,[87][88][89].…”
Section: Iron Oxide Nanoparticles (Ionps)mentioning
confidence: 99%
“…In this pioneering work, a hollow bimetallic oxide nanoparticle was produced by post-synthetic transformation using the oxidationreduction reaction between oxidized water, taking into account that the transition metal may have various oxidation forms. Although not directly applicable to biomedical applications, Mn and Fe used in the study have potential as MR imaging contrast agents and magnetic properties that allow site-specific concentration in vivo [237][238][239][240][241][242]. Based on the myriad of transition-metal nanoparticles present in the form of metal oxides and the ability to mass-synthesize them, this approach is an example of extended galvanic replacement and can be viewed as a new and feasible approach for the future.…”
Section: Other Transition Metal Elementsmentioning
confidence: 99%